A NOVEL AUTOLOGOUS MICROGRAFTS TECHNOLOGY IN COMBINATION WITH NEGATIVE PRESSURE WOUND THERAPY (NPWT) FOR QUICK GRANULATION TISSUE FORMATION IN CHRONIC/REFRACTORY ULCER - Takagi, Satoshi; Oyama, Takuto; Jimi, Shiro; Saparov, Arman; Ohjimi, Hiroyuki (MDPI, 2020)
Negative pressure wound therapy (NPWT) has been commonly used over the years for a wide range of chronic/refractory lesions. Alternatively, autologous micrografting technology is recently becoming a powerful modality for initiating wound healing. The case presented is of a patient with a lower leg ulcer that had responded poorly to NPWT alone for three weeks. Consequently, the patient was put on a combination therapy of NPWT and micrografting. After injection of a dermal tissue micrografts suspension into the entire wound bed, NPWT was performed successively for two weeks, resulting in fresh granulation tissue formation. Thereafter, the autologous skin graft was taken well. This case study indicates that for a chronic/refractory ulcer patient with poor NPWT outcome, combination therapy using micrografting treatment and NPWT could rapidly initiate and enhance granulation tissue formation, creating a favorable bedding for subsequent skin grafting.
Keywords: regenerative medicine; chronic wounds; micrografts; Research Subject Categories::MEDICINE